Analisis Persentase Jenjang Kognitif Dan Kualitas Butir Soal Ujian Sekolah Mata Pelajaran Ilmu Pengetahuan Alam Kelas VI SDN Pendopo Kabupaten Empat Lawang Tahun Pelajaran 2020/2021 - Fabil Fabil; Irwan Koto; Endang Widi Winarni (Jurnal Kajian Pendidikan Dasar (Kapedas), 2022)
This study aims to describe the cognitive appearance and quality of empirical questions about school exams. This type of research is descriptive quantitative research. The subject of this research is a matter of school exams for science subjects. The object of research is the description and quality of the items empirically. The research instrument was in the form of an analysis of the percentage level of knowledge and quality of items empirically. The research data were analyzed using proportions calculated by percentage and rater agreement as well as student scores tested for validity, reliability, level of difficulty, and discriminatory power. The results showed that: 1) The percentage of questions at Level 1 was 52.50%. At Level 2, 22.50% is less than the ideal standard of BSNP. At Level 3 of 25%, and 2) The quality of the items empirically, the results of the validity of 22 questions are valid and 18 questions are not valid, the results of the reliability test are 0.629, the difficulty level test is 5 easy questions (12.5%), 27 questions moderate (67.5%) and 8 difficult questions (20%,) the results of the discriminatory test were 25 bad questions (62.5%) and 15 questions were sufficient (37.5%). Thus, the quality of the science test items for grade VI students of SDN Pendopo, Empat Lawang Regency 2020/2021 is not good, judging from the comparison of the level of knowledge and quality empirically.